Optimal power flow in distribution network considering spatial electro-thermal coupling effect - Shu, Jun; Guan, Rui; Wu, Lei (IET generation, transmission & distribution, 2017)
The conductor resistance changes in accordance with the conductor temperature, in turn the line thermal capacity limit and power flow are influenced by its spatial characteristics of line routes and surrounding weather conditions. In light of the significant difference of spatial characteristics of line routes and weather conditions in different regions covered by distribution network, a novel optimal power flow (OPF) model in distribution network considering spatial electro-thermal coupling effect is proposed to integrate heat transfer constraints and electro-thermal coupling constraints into normal distribution network operation constraints. To address the computational complexity of the proposed model, the line thermal capacity limit is calculated firstly using the spatial steady-state heat balance equation. Then, a genetic algorithm combined with an extended back/forward sweep method is presented to solve the distribution system OPF problem, in which the heat balance equation is embedded in the forward sweep stage of the power flow calculation. Consequently, line temperatures, resistances, and power flows are dynamically updated during the iterative procedure. A 14-bus system with nine regions shows that the spatial electro-thermal coupling effect has a significant impact on the result of power flow and the optimal dispatch of the distributed generation in the distribution network.